Microencapsulated frankincense essential oil: a potential remedy and prevention of mouth diseases - Barre, Mohamed Soleiman; Ali, Fathilah; Mirghani, Mohamed Elwathig Saeed; Nordin, Noor Faizul Hadri (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2019)
The global burden of disease studies estimated that oral diseases affected half of the world’s population (3.58 billion people) with dental caries (tooth decay) in permanent teeth being the most prevalent condition assessed. On the other hand, the increasing resistance of dental caries towards the available antimicrobials and extensive use of the controversial synthetic chemicals to overcome these problems have attracted the scientific community’s attention to the search for new cost-effective remedies of natural products. Frankincense or Boswellia species are highly important aromatic plants belonging to the Burseraceae family. The present study will focus on an in-vitro anti-inflammation and anti-bacterial activity of Boswellia carterii (BC) Essential oil (EO) encapsulated into the Gum Arabic (GA) polymer. Thus, certain mouth pathogenic bacteria, which are the main contributors to dental caries and gingivitis, namely (Streptococcus mutans and Lactobacillus species), and their in-vitro responses to the defined micro-particles, will pave the way to introduce a new potential remedy to the forth mentioned problems.